The assessment of the possibilities for the Lithuanian fleet to comply with new environmental requirements - Panasiuk, Irina; Lebedevas, Sergejus (Transport, 2014)
The article analyses the economic impact of compliance of the Lithuanian fleet with the new requirements of the MARPOL 73/78 Annex VI, which sets a limit for sulphur content in marine fuel to 0.1% in 2015 in Emission Control Area (ECA) and to 0.5% in 2020 globally. The assessment of several most realistic options of complying with the new requirements is presented in the article. Each of these methods is assessed by means of uncovering the economic and practical issues associated with applying their implementation to the Lithuanian fleet. An overview of Lithuanian fleet was carried out to choose the particular vessels for analysis. A group of 10 vessels was selected to compare the benefits and limitations of using low sulphur fuel and scrubbers. The economic impact of using low sulphur fuel or installing the scrubber for each vessel is also assessed in the article.First Published Online: 25 Mar 2014